Love, Stargirl - Spinelli, Jerry (New York : Knopf, 2007)
Still moping months after being dumped by her Arizona boyfriend Leo, fifteen-year-old Stargirl, a home-schooled free spirit, writes "the world's longest letter" to Leo, describing her new life in Pennsylvania.
Kirkus Starred.
Publisher's Weekly.
Voice of Youth Advocates (V.O.Y.A.).
4.1
5-8
Keywords: Diaries -- Fiction; Eccentrics and eccentricities -- Fiction; Home schooling -- Fiction; Letters -- Fiction; Love -- Fiction; Diaries -- Fiction; Eccentrics and eccentricities -- Fiction; Home schooling -- Fiction; Letters -- Fiction; Love stories; Pennsylvania -- Fiction; Pennsylvania -- Fiction